Answer:
y = -x + 1
Step-by-step explanation:
eqn of line: y=mx+c
perpendicular, m1 x m2 = -1
m × 1 = -1
m = -1
y=-x+c
sub x=-5, y=6
6 = -(-5) +c
6 = 5 + c
c = 1
y = -x + 1
Answer:
Step-by-step explanation:
1)y=-6x-14 ---------(i)
-x-3y=-9 ---------- (ii)
Substitution method:
Substitute y value in equ (i)
-x -3*(-6x-14) = -9
-x - 3*-6x -3*(-14)= -9
-x + 18x + 42 = -9
17x = -9 -42
17x = -51
x = -51/17
x = -3
Substitute x value in equation (i)
y = -6*-3 -14
y =18-14
y = 4
Answer:
D
Step-by-step explanation:
Answer:
4,314.6
Step-by-step explanation:
522.98 multiplied by 8.25 is 4,314.585 which rounded to the nearest cent is 4,314.6